2022
DOI: 10.1101/2022.05.01.490234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Angiotensin II regulates the neural expression of subjective fear in humans - precision pharmaco-neuroimaging approach

Abstract: There has been growing interest in using pharmacological fMRI to identify novel treatments for fear, yet these models are limited with respect to determining process-specific effects on the actual subjective experience of fear which represents the key symptom why patients seek treatment. Combining a selective angiotensin II type 1 receptor (ATR1) antagonist with a fear vigilance fMRI paradigm and neurofunctional decoding in n = 87 individuals we demonstrate that AT1R blockade selectively reduces the neurofunct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…In line with such clinical effects, we have recently shown that a single dose of the ARB losartan prevents a physiological stress response and facilitates contextual processing during experimental trauma, two processes known to be relevant to the development of posttraumatic stress disorder (PTSD,16). Similarly, administration of losartan has been associated with reductions in subjective fear during a aversive task (17) and encoding of negative memories (18). Identifying specific aspects of learning (e.g., prediction errors or learning rates) impacted by RAS-modulating drugs can help us understand the function they play in the prevention of anxiety development.…”
Section: Main Text Introductionmentioning
confidence: 79%
“…In line with such clinical effects, we have recently shown that a single dose of the ARB losartan prevents a physiological stress response and facilitates contextual processing during experimental trauma, two processes known to be relevant to the development of posttraumatic stress disorder (PTSD,16). Similarly, administration of losartan has been associated with reductions in subjective fear during a aversive task (17) and encoding of negative memories (18). Identifying specific aspects of learning (e.g., prediction errors or learning rates) impacted by RAS-modulating drugs can help us understand the function they play in the prevention of anxiety development.…”
Section: Main Text Introductionmentioning
confidence: 79%